The Fatal Fang: did stress-induced Xerostomia evolve as a strategic offensive/ defensive weapon in hominid combat? - Sunkavally Satyendra; Lalitha Pappu (International Journal of Life Sciences, 2015)
The lack of the traditional natural weapons of combat-horn, claw, extended canine, talon, venom etc. has forced the human species to develop a rather novel and unorthodox biological weapon, namely stress-induced xerostomia, or a reduction in salivary flow into the oropharyngial cavity, during those times of psychological stress that are the usual prelude to combat. Since one of the immunologic functions of the saliva is to keep down the number of micro-organisms in the oral cavity, this reduction of salivation immediately results in a marked increase in the bacterial population of the mouth. Since bites are frequently inflicted in combat between humans, this would result in the inoculation of a substantial bolus of pathogenic micro-organism into the bite wound of the opponent, the subsequent setting up of an infective nidus at the bite site, and thus either in fever/sickness or a severe festering wound necessitating, not infrequently, in a need for frank amputation of the affected digit. In any event the combat ability of the opponent will be substantially reduced as a result. It is therefore likely that there has been a substantial Darwinian selection for this peculiar physiologic trait of a desiccation of the mouth during times of inter-personal stress, when the likelihood of there being a physical conflict between humans rises substantially.